Sirtuins in osteoarthritis: current understanding - Liu, Yikai; Zhang, Zian; Liu, Chang; Zhang, Haining (Frontiers in Immunology, 2023)
Osteoarthritis (OA) is a common disease characterized by severe chronic joint pain, that imposes a large burden on elderly people. OA is a highly heterogeneous disease, and multiple etiologies contribute to its progression. Sirtuins (SIRTs) are Class III histone deacetylases (HDACs) that regulate a comprehensive range of biological processes such as gene expression, cell differentiation, and organism development, and lifespan. Over the past three decades, increasing evidence has revealed that SIRTs are not only important energy sensors but also protectors against metabolic stresses and aging, and an increasing number of studies have focused on the functions of SIRTs in OA pathogenesis. In this review, we illustrate the biological functions of SIRTs in OA pathogenesis from the perspectives of energy metabolism, inflammation, autophagy and cellular senescence. Moreover, we offer insights into the role played by SIRTs in regulating circadian rhythm, which has recently been recognized to be crucial in OA development. Here, we provide the current understanding of SIRTs in OA to guide a new direction for OA treatment exploration.